1-Hydroxypyranonaphthoquinones – Isolation, Bioactivity and Synthesis - D. Donner, Christopher (Mini-Reviews in Organic Chemistry, 2015)
A discussion of 1-hydroxypyranonaphthoquinones is presented that outlines the isolation and biological activity of the known naturally occurring members of this class of compounds. Synthetic approaches developed towards 1- hydroxypyranonaphthoquinones and analogues having potentially improved biological profiles are discussed with particular emphasis on the HRV 3C-protease inhibitor thysanone.
Keywords: lactol